2003
DOI: 10.1161/01.hyp.0000088852.28814.e2
|View full text |Cite
|
Sign up to set email alerts
|

Aged Spontaneously Hypertensive Rats Exhibit a Selective Loss of EDHF-Mediated Relaxation in the Renal Artery

Abstract: Abstract-Endothelium-dependent relaxation is frequently attenuated in hypertension. We hypothesized that the contribution of the endothelium-derived hyperpolarizing factor (EDHF) to the acetylcholine (ACh)-induced, endotheliumdependent relaxation is attenuated with aging in the renal artery of spontaneously hypertensive rats (SHR) compared with age-matched Wistar-Kyoto (WKY) rats. ACh-induced, NO-mediated relaxation was identical in young (8-weekold) WKY and SHR, whereas EDHF-mediated relaxations (assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 48 publications
6
60
1
1
Order By: Relevance
“…Upregulation of EDHF during hypertension has also been reported in renal arteries of SHR. 18 In that study, EDHF-mediated responses were upregulated at the age of 2 months, whereas EDHF-mediated responses were virtually abolished at the age of 22 months compared with agematched Wistar-Kyoto rats. 18 It is therefore plausible to speculate that although long-term exposure to hypertension would ultimately diminish EDHF-mediated responses, EDHF-mediated responses may be upregulated to maintain overall endothelial function in the early phase of hypertension.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Upregulation of EDHF during hypertension has also been reported in renal arteries of SHR. 18 In that study, EDHF-mediated responses were upregulated at the age of 2 months, whereas EDHF-mediated responses were virtually abolished at the age of 22 months compared with agematched Wistar-Kyoto rats. 18 It is therefore plausible to speculate that although long-term exposure to hypertension would ultimately diminish EDHF-mediated responses, EDHF-mediated responses may be upregulated to maintain overall endothelial function in the early phase of hypertension.…”
Section: Introductionmentioning
confidence: 77%
“…18 In that study, EDHF-mediated responses were upregulated at the age of 2 months, whereas EDHF-mediated responses were virtually abolished at the age of 22 months compared with agematched Wistar-Kyoto rats. 18 It is therefore plausible to speculate that although long-term exposure to hypertension would ultimately diminish EDHF-mediated responses, EDHF-mediated responses may be upregulated to maintain overall endothelial function in the early phase of hypertension. As impairment of EDHF would induce endothelial dysfunction, which may lead to the progress of atherosclerosis, 19 it is of clinical importance to reveal the underlying mechanisms of the upregulation of EDHF during hypertension.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Cx40-deficient mice are hypertensive, suggesting that impaired EDHF-mediated renal vasodilatation may play a role in HTN (31). Also, while EDHF-mediated renal vascular relaxation is normal in young SHR, it is reduced in aged SHR and associated with depolarized resting membrane potential of the renal artery VSM (15), suggesting that decreased EDHF may be involved in the progression of HTN.…”
Section: Renal Endothelial Cell Dysfunction In Htnmentioning
confidence: 99%
“…Scavenging of superoxide or inhibition of enzymatic sources of superoxide within the vascular wall has resulted in an improvement in the vasodilatator capacity of both patients with hypertension (Taddei et al, 1998) and hypertensive rats (Dobrian et al, 2001;Hamilton et al, 2002;Ulker et al, 2003), and this has been attributed to an increased bioavailability of NO (Schnackenberg et al, 1998). However, the impaired endothelium-derived hyperpolarizing factor (EDHF) type vasodilatation observed in arteries from hypertensive animals (Fujii et al, 1992;Bussemaker et al, 2003) has also been shown to be restored by scavenging of superoxide in hypertensive rats (Adeagbo et al, 2003). In rat isolated skeletal arterioles, elevated intravascular pressure through activation of protein kinase C leads to increased superoxide formation and impaired flow-evoked vasodilatation (Huang et al, 1998;Ungvari et al, 2004), suggesting that superoxide formation is due to high pressure per se.…”
Section: Introductionmentioning
confidence: 99%